Собачье сердце: [сборник] / Михаил Булгаков - Булгаков Михаил Афанасьевич (Лучшая мировая классика, 2019)
Экземпляры: ф.16 (20201026) / Инвентарный номер: 60382 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6-44